(untitled) (Journal of Scientific Research, 2021)
Ruminant, especially cattle and goats constitute the major portion of the livestock which are usually suffered from a wide range of diseases. Hence, this study was designed to determine clinical cases of cattle and goat in relation to different parameter. A total of 106 sick ruminants (cattle = 56, goat = 50) in different area of Bera upzilla, Pabna were investigated during March to September, 2016. The parasitic infestation (32.1%) in cattle and viral diseases (36%) in goat were higher. In relation to sex, the disease frequencies were higher in female goat of 56.0% and reproductive diseases in female cattle of 66.7%. Among the clinical case, 70% was in black bangle goat. On the other side, the vaccination and grazing system had strong significant (p<0.01) association with disease frequencies having the chi-square value of 36.036 and 35.617, p<0.01, with Phi (φ) coefficient of 0.583 and -0.580 respectively. Besides this, the male owner of clinically sick animal was higher of 71.40% for cattle and 52% for goat with chi-square value, (N=106) = 4.244, p<0.05, φ coefficient of 0.20 indicating a significantly moderate association. However, these two ruminants (cattle and goat) are mostly vulnerable to parasitic infestation and viral diseases.